Pengaruh Model Pembelajaran Creative Problem Solving (CPS) terhadap Kemampuan Berpikir Kreatif Siswa pada Materi SPLDV di SMP Negeri 1 Panei - Siva Anastasia Munthe; Lois Oinike Tambunan; Golda Novatrasio Sauduran (Journal on Education, 2023)
The purpose of this study was to find out whether there was an effect of the Creative Problem Solving (CPS) Learning Model on Students' Creative Thinking Ability in SPLDV Material at SMP Negeri 1 PANEI which consisted of 30 students. This study uses a type of quantitative research with the Pra-Experimental design research method. The population in this study was class VIII with 7 classes at SMP Negeri 1 PANEI with 210 students. The number of samples taken was 30 students, namely class VIII-E Data collection techniques used pre-test and post-test. The results of the study were to find out how much influence the Creative Problem Solving (CPS) Learning Model had on Students' Creative Thinking Ability in SPLDV Material at SMP Negeri 1 PANEI. The ability to think creatively based on the pre-test and post-test questions is high with an average score of 68,16 and 83,16.